If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(6x + 10) = -2(x + -2) Reorder the terms: 4(10 + 6x) = -2(x + -2) (10 * 4 + 6x * 4) = -2(x + -2) (40 + 24x) = -2(x + -2) Reorder the terms: 40 + 24x = -2(-2 + x) 40 + 24x = (-2 * -2 + x * -2) 40 + 24x = (4 + -2x) Solving 40 + 24x = 4 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 40 + 24x + 2x = 4 + -2x + 2x Combine like terms: 24x + 2x = 26x 40 + 26x = 4 + -2x + 2x Combine like terms: -2x + 2x = 0 40 + 26x = 4 + 0 40 + 26x = 4 Add '-40' to each side of the equation. 40 + -40 + 26x = 4 + -40 Combine like terms: 40 + -40 = 0 0 + 26x = 4 + -40 26x = 4 + -40 Combine like terms: 4 + -40 = -36 26x = -36 Divide each side by '26'. x = -1.384615385 Simplifying x = -1.384615385
| (4/x-7)-(5/x+7)=(2/x^2-49) | | log(8)(5x+5)=log(8)(5x+2) | | 8-1/2n=12 | | (-6+34)/(-14)+2 | | f(x)=4x^2+7x-15 | | (X/2)-(2/3)=(1/4) | | 8-5x=38 | | 2/7x=-6/35 | | 2(1.5c+4)=(-1) | | 5+5(2-x)=-3(x+5) | | a/4+4=88 | | x^2-2=5x^2-12x-2 | | 4+5(2-x)=-2(x+5) | | 10v^2-53v+36=0 | | y=2x^2-11x+9 | | (X^2+9x+20)/(x+15) | | f(x)=5x^2-6x-8 | | f(x)=5x^2-6x-8 | | 3x+17y=-23 | | D=Prk | | 8x+4=26-2x | | 4(3+x)=5(4x-1)-47 | | 9z+5-2z=59-2z | | 8x-2(2-x)=13 | | (1/2)y-(2/3)=7/8 | | x-10=12-x | | 6ln(x)=-1 | | 8w*2=50 | | 6lnx=-1 | | 180-7x=29+16 | | x+6y-5x-11y+2x= | | 35x-7=35x-7 |